Investigating the photo-induced ultrafast insulator-metal phase transition in organic Cu(DCNQI)2 salts by ultrafast electron diffraction - Smit, Albert Bart (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhD)--Stellenbosch University, 2018.